Professional Competence of Akidah Akhlak Teachers in Madrasah Aliyah Negeri - Ira Suryani (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article aims to determine the professional competence of Akidah Akhlak teachers in carrying out the teaching and learning process. This research uses a qualitative descriptive method, which describes and interprets objects according to what they are to describe the overall situation or event. The results of the study revealed that Akidah Akhlak Madrasah Aliyah Negeri 2 Medan Model has not fully implemented the professional competency indicators contained in Law Number 14 of 2005. Some of the indicators that have been applied include having knowledge and mastery of the field of study being fostered, indicators of having the right attitude towards oneself, peer schooling, and the field of study being fostered, and indicators of having teaching skills. The findings reveal that indicators that have not been fully implemented are indicators of knowing the learning and behavior of learners.